Automobile Industry Supply Chain in Thailand - Itoh, Munehiko; Kato, Atsumi; Shimono, Yoshitaka; Haraguchi, Yasuhiko; Taehoon, Park (Kobe University Social Science Research Series, 2018)
XIII, 107 p. 19 illus., 1 illus. in color.